Thou shalt not pass?: Examining the existence of an immigrant glass ceiling in Sweden, 1970-1990 - Jonas Helgertz (Demographic Research, 2011)
The paper studies a sample of natives and 18 immigrant nationalities in the Swedish labor market between 1970 and 1990. The purpose is examining the existence of an immigrant specific glass ceiling. Results suggest a considerable overall advantage in terms of the probability of experiencing upward occupational mobility for native Swedish males. Despite this, the pattern does not correspond to the theoretical expectations of a glass ceiling. Using the ISEI classification of occupational status, the advantage experienced by Swedish males is consistent in the private manufacturing and private service sectors, compared to the experience of immigrants and women. The public sector generally suggests a similar pattern according to linguistic background. In this sector, certain groups of women are, however, observed to experience an advantage from low occupational status origins.